Health Benefit of Coconut Milk - Suyitno T. (Indonesian Food and Nutrition Progress, 2003)
Indonesia, India and the Philippines are the major world coconut producers. Of the three leading producers, the Philippines is the biggest supplier to world trade in the form of coconut oil. Indonesia and India use the bulk of their coconut internally, both as food nuts and as coconut oil. The main use of coconut in Indonesia is for coconut milk. Indonesians are reported as moderate coconut milk consumers, with a per capita consumption of 6.5-8.2 kilograms. Coconut milk is an important part of the dietary in coconut producing countries like Indonesia. It is valued mainly for its characteristic nuttyflavor and for its nutritional content. Coconut milk is used as an ingredient in many fish, shellfish, meat, poultry, vegetable dishes, yellow rice, delicious rice (nasi gurih), confectionaries, and baked goods. The main component of coconut milk is coconut oil, it account for 38% by weight. Coconut oil is naturally saturated, about 92% consists of saturated fatty acids., mainly are medium chain fatty acids (MCFA). About 50 % offatty acid in coconut oil is lauric (CI), for this reason, it is called the "lauric oil". For years, coconut oil has been the undeserving target of negative publicity generated by the North American Soy Oil Industry and consumer activist groups. The main reason for the negative publicity campaign is money; coconut oil is a third-world commodity and it is in direct competition with hydrogenated soy oil. Some researches shown that in fact saturated fat in coconut had no harmful effect to the human, because mainly consist of MCFA, especially lauric acid. Laurie acid is a medium chain fatty acid, ,found naturally in mother's milk. Laurie acid has the beneficial function of being formed into monolaurin in the body. Monolaurin is the antiviral. antibacterial, and antiprotozoal, monoglyceride used by the body to destroy lipid-coated viruses such as cytomegalovirus (CMV), HIV, herpes, and influenza. Adults could probably take benefit from the consumption of 10 to 20 grains of lauric, acid per day. Based on the per capita intake of coconut oil. the per capita daily intake of lauric acid can be approximated, The daily intake of lauric acid in India is about 16 grams, the Philippines 7.3 grams, Indonesia 4.7 grams and Singapore 2.8 grams. For Indonesians, 4.7 grains lauric acid daily intakes is stilIfarfr0111 10-20 grams. As a major coconut producing country, it can he increased easily by means of increasing coconut milk consumption through consuming many kind of delicious Indonesian daily foods.